Distribution of Native Lactic Acid Bacteria in Wineries of Queretaro, Mexico and Their Resistance to Wine-Like Conditions - Miranda-Castilleja, Dalia E.; Martínez-Peniche, Ramón Álvar; Aldrete-Tapia, J. A.; Soto-Muñoz, Lourdes; Iturriaga, Montserrat H.; Pacheco-Aguilar, J. R.; Arvizu-Medrano, Sofía M. (Frontiers in Microbiology, 2016)
Native lactic acid bacteria (LAB) are capable of growing during winemaking, thereby strongly affecting wine quality. The species of LAB present in musts, wines during malolactic fermentation (MLF), and barrels/filters were investigated in wineries from the emerging wine region of Queretaro, México using multiplex PCR and culture. The resistance to wine-like conditions (WLC): ethanol (10, 12 and 13%), SO2 (30 mg·l-1) and low pH (3.5) of native LAB strains was also studied. Five species were detected within 61 samples obtained: Oenococcus oeni, Lactobacillus plantarum, Pediococcus parvulus, Lactobacillus hilgardi and Lactobacillus brevis. Four species (excepting L. brevis) were found in must; O. oeni and P. parvulus were ubiquitous in wine and L. plantarum and L. brevis were mainly present at the initial stage of MLF, while L. hilgardii was mostly detected at the advanced stage. Furthermore, some species detected in barrel/filter, sprove them to be hazardous reservoirs. From 822 LAB isolates, only 119 resisted WLC with 10% ethanol; the number of strains able to grow in WLC with 13% ethanol decreased approximately by 50%, O. oeni being the most versatile species with 65% of resistant isolates, while Lactobacillus spp. and P. parvulus were the most strongly affected, especially those recovered from barrel/filter, with less than 10% of resistant isolates. This study evidences the presence of local strains able to be used as starter cultures, and also enabled the assessment of the risks derived from the presence of spoilage LAB strains resistant to WLC.